2018
DOI: 10.1021/acs.biochem.7b01238
|View full text |Cite
|
Sign up to set email alerts
|

Probing Structural Changes among Analogous Inhibitor-Bound Forms of HIV-1 Protease and a Drug-Resistant Mutant in Solution by Nuclear Magnetic Resonance

Abstract: In the era of state-of-the-art inhibitor design and high-resolution structural studies, detection of significant but small protein structural differences in the inhibitor-bound forms is critical to further developing the inhibitor. Here, we probed differences in HIV-1 protease (PR) conformation among darunavir and four analogous inhibitor-bound forms and compared them with a drug-resistant mutant using nuclear magnetic resonance chemical shifts. Changes in amide chemical shifts of wild-type (WT) PR among these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…Accordingly, we previously designed, synthesized and evaluated a panel of 10 DRV analogs with varying P1' and P2' moieties, and demonstrated that substrate envelope-guided design can achieve improved inhibition and potency against resistant variants 34 . These inhibitors, named UMass1-10, have subsequently served us as tools to probe subsite interdependency 35 , water structure 36 , and structural changes in solution by NMR 37 . Among these analogs, UMass1 and UMass6 share the same P2' moiety with DRV but have larger hydrophobic groups at the P1' position [ Figure 2a] leveraging the unexploited space in the S1' pocket of the substrate envelope.…”
mentioning
confidence: 99%
“…Accordingly, we previously designed, synthesized and evaluated a panel of 10 DRV analogs with varying P1' and P2' moieties, and demonstrated that substrate envelope-guided design can achieve improved inhibition and potency against resistant variants 34 . These inhibitors, named UMass1-10, have subsequently served us as tools to probe subsite interdependency 35 , water structure 36 , and structural changes in solution by NMR 37 . Among these analogs, UMass1 and UMass6 share the same P2' moiety with DRV but have larger hydrophobic groups at the P1' position [ Figure 2a] leveraging the unexploited space in the S1' pocket of the substrate envelope.…”
mentioning
confidence: 99%
“…Except for the experimental studies, different simulation methods were also employed to partially probe drug resistance induced by the mutated PR . It is worth noting that Schiffer's group used crystallography and simulations to study bindings of inhibitors to PR, and their results clarified drug‐resistant mechanism of mutations in PR and binding modes of inhibitors to PR . Although more traditional approaches, namely design and development of inhibitors targeting the active site, are adopted by many research groups to overcome drug resistance of PR, by now it is still a big challenge to solve this issue.…”
Section: Introductionmentioning
confidence: 99%
“…5c) and DRV-bound forms (Fig. 5d) [60]. Flap+ (I54) spectra also exhibited very similar resonance patterns to those of Flap+ (I54V) in both forms ( Fig.…”
Section: Nmr Probed Pr Conformationmentioning
confidence: 61%
“…The clones were confirmed by DNA sequencing. We expressed 15 N isotope labeled proteins and purified using the protocols published previously [60]. Proteins were folded with 10 mM acetate at pH 6.0, buffer exchanged to a 20 mM sodium phosphate at pH 5.8, and concentrated approximately to 5 or 50 µM (assuming a dimer).…”
Section: Protease Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation